In vitro antimicrobial efficacy of photodynamic therapy in bacteria and fungi - Chia, Maureen Shi En (2015)
Photodynamic therapy (PDT) using riboflavin and ultraviolet-A (UV-A) combination is well recognized as a treatment for keratoconus to strengthen the collagen cross-linking in cornea. Although studies have shown that photo-activated riboflavin also inactivates pathogens, better understanding about its antimicrobial efficacy is essential before it becomes a treatment for infectious keratitis. Through three different in vitro assays, we aim to evaluate the antimicrobial efficacy of PDT using riboflavin and UV-A combination on bacteria (Pseudomonas aeruginosa and Staphylococcus aureus) and fungi (Candida albicans). From growth inhibition assay, all bacterial species showed clear inhibition zone when exposed to the combined treatment. A comparison between the measured inhibition zones suggests that S. aureus is more susceptible than P. aeruginosa. Yet, C. albicans is resistant to the combined treatment on culture plates. Results from colony forming units assay showed that S. aureus has the highest reduction in bacterial count of 12.9%, then 8.6% for P. aeruginosa and 1.9% for C. albicans. Minimal variation was found between the combined treatment and UV-A alone treatment. Surprisingly, optical density measurement demonstrated higher absorbance values after combined treatment for all microorganisms indicating greater metabolic activity. Overall, riboflavin and UV-A combination may succeed as a potential therapy for infectious keratitis.